ELOVL5 and IGFBP6 genes modulate sensitivity of breast cancer cells to ferroptosis - Nikulin, Sergey; Razumovskaya, Alexandra; Poloznikov, Andrey; Zakharova, Galina; Alekseev, Boris; Tonevitsky, Alexander (Frontiers in Molecular Biosciences, 2023)
Relapse of breast cancer is one of the key obstacles to successful treatment. Previously we have shown that low expression of ELOVL5 and IGFBP6 genes in breast cancer tissue corresponded to poor prognosis. ELOVL5 participates directly in the elongation of polyunsaturated fatty acids (PUFAs) that are considered to play an important role in cancer cell metabolism. Thus, in this work we studied the changes in lipid metabolism caused by the knockdown of either ELOVL5 or IGFBP6 gene in MDA-MB-231 cells. We found that the knockdown of IGFBP6 gene led to significant changes in the profile of fatty acids in the cells and in the expression of many genes associated with lipid metabolism. As some PUFAs are known to inhibit proliferation and cause death of cancer cells, we also tested the response of the cells to single PUFAs and to combinations of docosahexaenoic acid (DHA, a n-3 PUFA) with standard chemotherapeutic drugs. Our data suggest that external PUFAs cause cell death by activation of ferroptosis, an iron-dependent mechanism of cell death with excessive lipid peroxidation. Moreover, both knockdowns increased cells' sensitivity to ferroptosis, probably due to a significant decrease in the activity of the antioxidant enzyme GPX4. Addition of DHA to commonly used chemotherapeutic drugs enhanced their effect significantly, especially for the cells with low expression of IGFBP6 gene. Thus, for the patients with low expression of IGFBP6 and ELOVL5 genes addition of PUFAs to the treatment regimen can be potentially beneficial and is worth testing in a clinically relevant setting.